2019
DOI: 10.1088/1361-6439/ab31c8
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of strained-SiGe and bulk-Si channel FinFETs at 7 nm technology node

Abstract: Applications of stress/strain are now part of technology 'boosters' in microelectronics industry among other technologies such as silicon-on-insulator or the metal gate/high-k techniques. Application of strain in channel significantly increases carrier mobility. Thus, there is a need to characterize the deformations at nanoscale in the semiconductor induced by the strain. Uniaxial compressive strain has been an indispensable performance booster for p-channel FinFETs. In this work, based on extensive 3D process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…So, the slope of the transfer characteristics curve decreases and hence threshold voltage decreases. This is true even when stress is not introduced in the devices [41]. Moreover, the lowering stress increases the bandgap or vice versa and with the increase in stress, the bandgap decreases.…”
Section: Vertically Stacked Uniaxially Strained-sige Channel Nsfetsmentioning
confidence: 99%
See 2 more Smart Citations
“…So, the slope of the transfer characteristics curve decreases and hence threshold voltage decreases. This is true even when stress is not introduced in the devices [41]. Moreover, the lowering stress increases the bandgap or vice versa and with the increase in stress, the bandgap decreases.…”
Section: Vertically Stacked Uniaxially Strained-sige Channel Nsfetsmentioning
confidence: 99%
“…It has been observed that the carriers are dispersed more evenly among the sub-valleys, which is the primary factor in improving mobility. The stress-induced hole mobility enhancement can be given by [41]…”
Section: Device Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, multiple experiments or measurements can be performed, increasing the reliability of the data processing. In addition, simulated data based on a finite element model can be created to validate the accuracy of the data processing methods 136 …”
Section: Measurement Of Strain By Transmission Electron Microscopymentioning
confidence: 99%
“…In this regard, strained silicon, III-V materials, and germanium (Ge) are suggested as the future channel material as these provide higher electron mobility compared to silicon. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Out of these non-silicon materials, Ge graves the highest attention of device researchers due to its exceptionally high hole mobility. [17][18][19][20][21] As the current technology deals with CMOS architecture, we need both NMOS and PMOS to be implemented.…”
mentioning
confidence: 99%